A multilayered 3D hexahedral finite element with rotational DOFs - Meftah, Kamel; Sedira, Lakhdar; Zouari, Wajdi; Ayad, Rezak; Hecini, Mabrouk (European Journal of Computational Mechanics, 2013)
The study presents a multilayer eight-node hexahedral finite element with rotational degree of freedom to model composite laminate structures. Its formulation is based on virtual rotations of a nodal fibre within the element that enriches the displacement vector approximation. A particular attention is made to the determination of transverse deflections as well as inplane stresses. To assess the accuracy of the proposed element, several benchmarks are considered and the obtained results are compared with 3D elasticity solutions and other advanced finite elements from the literature.